(3EbJUGOjGJ GdJYdje hJNWjWgs - (3adjM MSjf(B, (3Ndas ((3YeGf(B:s (3YGde GdcJH GdMOjK,s, 2007)
(3jVe GdLhGfH GdGbJUGOjI(B:(3aj GdGbJUGO, GdJNda GdGbJUGOj, GdJfejI GdGbJUGOjI, GdJNWjW GdGbJUGOj, GdehGQO GdHTQjI, GbJUGOjGJ GdJYdje(B: (3GdCgejI GdGbJUGOjI ddJYdje hbjeJg GdGbJUGOjI, Jehjd GdJYdje, GdGfaGb Ydi GdJYdje hJcGdjag, YGFc GdJYdje, GdcaGAI GdGfJGLjI ddJYdje, JNWjW GdJYdje(B: (3eGgjI GdJNWjW GdJYdjej, eJWdHGJ GdJNWjW GdJYdjej, WQb hCSGdjH GdJNWjW GdJYdjej, cjajI GYOGO GdNWI GdJYdjejI, UYhHGJ heTcdGJ GdJNWjW GdJYdjejs
(3HjHdjhZQGajG(B: (3U(B.391s
Keywords: (3GdGbJUGOs; (3GdJNWjWs; (3GdJYdje(B- (3GbJUGOjGJs